2016
DOI: 10.1002/lary.26322
|View full text |Cite
|
Sign up to set email alerts
|

Risk of progressive hearing loss in untreated superior semicircular canal dehiscence

Abstract: 4. Laryngoscope, 127:1181-1186, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The reason for a mixed or conductive loss can be explained by the third window effect. Sensorineural hearing loss is not unknown either (16, 17, 24, 25) and in this series it was observed in 2 children. These children did not show any balance symptoms and the reason they were requested for a high resolution CT was because their MRI was normal as suggested in the aetiological diagnosis algorithm.…”
Section: Discussionmentioning
confidence: 49%
“…The reason for a mixed or conductive loss can be explained by the third window effect. Sensorineural hearing loss is not unknown either (16, 17, 24, 25) and in this series it was observed in 2 children. These children did not show any balance symptoms and the reason they were requested for a high resolution CT was because their MRI was normal as suggested in the aetiological diagnosis algorithm.…”
Section: Discussionmentioning
confidence: 49%
“…Among a series of patients with incidental or minimally symptomatic SSCD described by Patel et al, it was found that the median AC PTA was 18.5 dB, while the mean AC PTA was 38.0 dB among this cohort of patients, when matched for age. 16 When evaluating the BC PTA among this cohort of patients, the mean was 24.3, compared to the BC PTA from Patel et al that was 13.3 dB. Thus, this cohort of patients is found to have a worse bone line than in previously published cohorts.…”
Section: Discussionmentioning
confidence: 59%
“…15 If symptoms are mild, many patients elect to defer surgery, owing to the lack of demonstrated hearing decline with observation. 16 In the present study, we describe a series of patients who presented with symptoms and imaging consistent with SSCD syndrome after trauma, suggesting that a patient's trauma could push them "over the edge" in terms of developing SSCD syndrome symptoms. We theorize that these patients likely have a thin layer of endosteum still covering the dehiscence that is compromised with an abrupt increase in intra-vestibular or intracranial pressure-a so-called, "unmasking" of the condition in a patient who is already anatomically predisposed (Fig.…”
Section: Discussionmentioning
confidence: 83%
“…It appears that the hearing loss does not significantly change over time (68). There have been reported cases of worsening conductive hearing loss over time and cases have been reported in which symptoms progressed over many years (35, 47, 69), while at least one case developed rapid mixed hearing loss (70).…”
Section: Symptomsmentioning
confidence: 99%